Efektifitas Pembelajaran Remidial Dalam Meningkatkan Ketuntasan Belajar Peserta Didik Pada Pelajaran Pai Sd YPPSB 3 Sangatta Utara Tahun Pelajaran 2019/2020 - Akhmad Syam’un; Filminita Rini (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2020)
The purpose of this study was to determine the effectiveness of remedial learning as an effort to improve students learning mastery in PAI lessons. In this study used the method of questionnaires, documentation, observation and interviews (interviews). The result of this study is that there is a significant effectiveness in remedial learning as an effort to improve students learning mastery in PAI lessons. It can be seen from the calculation of the two variables obtained r = 0.5106 which means there is a sufficient correlation, and the coefficient of determination r2 = 0.2607 or 26.07% which means the effect of remedial learning in PAI lessons is 26.07% in achieving mastery learning. From the regression analysis obtained the equation Y = 18.05+0.62X.